KONFLIK TOKOH UTAMA DALAM NOVEL PULANG KARYA LEILA S. CHUDORI - Setiawan, Yogi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â AbstractThe background of this research is about the conflict experienced by the main character in the story line by presenting the conflict that arises in itself and something that is outside of himself. The method in this research is descriptive with qualitative form. The approach used is behavioristic psychology. Internal conflicts of main characters Dimas Suryo include; Feelings of jealousy, feelings of sadness, irritation, anxiety, confusion, feelings of longing, anger, feelings of worry, feelings of regret, feelings of unhappiness and feelings of emotion. The external conflicts of the main character Dimas Suryo include social conflicts. Social conflicts experienced by Dimas Suryo include; debates that took place between Dimas Suryo and Mas Hananto for removal Bang Amir, squabbles between Dimas Suryo and Mas Hananto romance Mas Mananto, the debate between Dimas Suryo and Mas Hananto on consistency in the choice of life, the debate between Dimas Suryo and Vivienne, Mas Nugroho criticize recipe Food whistling unclearly, Sumarno's presence to the Homeland Restaurant, a meeting between Dimas Suryo and Narayana in a special place and Lintang rebukes Dimas Suryo for his behavior towards Narayana.Â Keywords: conflict, character, behavioristic psychology.Â